Study of Community Capacity in Dealing with The Threat of Shore Erosion in Kragan Subdistrict Rembang District - Nur Hamid (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2018)
The shore erosion in Rembang District during 2003-2014 resulted in huge losses. This study was conducted in the Coastal District of Kragan because of frequent shore erosion. Coastal of Sumurtawang and Kragan have erosion. Coastal of Pandangan Wetan, Balongmulyo, and Tanjungan are stable due to the construction of a small port in the village of Karanganyar which affects the surrounding area. The capacity of indigenous knowledge is as high as local wisdom, perception and attitude of the community in handling shore erosion. Coping strategies is also as high as the value of human capital, social, financial, natural, and physical. There is a correlation between community capacity variables, it means that if the capacity of indigenous knowledge is high, then the coping strategies is also high. But, the capacity of indigenous knowledge does not significantly affect the coping strategies. The relation of these capacities determines the priority of settlement.